Excel Wealth Management Ltd : guiding a client through financial planning - Lim, Chee Chee; Ooi, Sue Chern; Chung, Muh Sha (London : SAGE Publications: SAGE Business Cases Originals, 2023)
This case follows John, a financial planner from Excel Wealth Management Ltd who is trying to guide his client, Esther, in her financial planning. Students will assume the role of John, the financial planner, in helping his client to make a financial decision that is in line with her financial needs. In the process of guiding the client through financial planning, the financial planner will help his client (a) to identify her financial goal, specifically whether she needs protection or wealth accumulation; (b) to understand the two different types of financial products she could consider, namely life insurance and term deposit; (c) by providing details about the costs and benefits of life insurance in her situation; and (d) by showing her the account balance in a bank term deposit.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Finance, Personal -- Case studies; Investments; Life insurance